Characteristics and Consequences of Medication Errors in Pediatric Patients Reported to Ramathibodi Poison Center: A 10-Year Retrospective Study - Tansuwannarat P. (2023)
Purpose: This study was performed to evaluate the clinical characteristics of, consequences of, and factors associated with medication errors (MEs) that cause harm to pediatric patients (<15 years of age) treated in the hospital setting. Patients and Methods: We performed a 10-year retrospective study (January 2011–December 2020) by analyzing data from the Ramathibodi Poison Center. MEs were classified into categories A to I according to the severity of the outcome. Results: In total, 121 patients were included in the study. Most (51.24%) patients were male. Their median age was 1 year (range, 1 hour–14 years). Infants, newborns, and toddlers were the three most common age groups in which MEs were reported. Most MEs occurred during the afternoon shift [n = 60 (49.59%)] and in the inpatient department (66.12%). The most common type of MEs was a dose error (64.46%). Antibiotics, sedative agents, and bronchodilators were the three most common classes of ME drugs. Four patients died. Three deaths occurred because of a dose error. One patient was a 1-year-old girl who received an iatrogenic intravenous phenytoin overdose of 10 times the normal dose, resulting in a phenytoin level of 72.4 mcg/mL. She died 22 hours after the ME occurred. The work shift was the only factor that significantly differed between patients with category C and D MEs and those with category E to I MEs. Conclusion: Small children were at highest risk for MEs. MEs induced harm and deaths in some patients. A preventive and safety system, including appropriate shift work administration, should be emphasized and implemented to prevent and/or decrease the occurrence of MEs.